1907 Texas Gen. Laws 210, An Act Defining "Burglary with Explosives," Prescribing Penalty for the Commission Thereof, and Declaring an Emergency, §§ 1-2. - (:unkn) unknown (My University, 1907)
Any person who shall commit burglary as defined by the Penal Code of this State, and in the commission of the offense uses nitro-glycerine, dynamite, gunpowder or other high explosives, shall be deemed guilty of burglary with explosives.
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME